The effect of chief sustainability officers on sustainability reporting—A management perspective - Toni W. Thun; Henning Zülch (Business Strategy and the Environment, 2022)
More and more companies worldwide are appointing a chief sustainability officer (CSO) to anchor the topic of sustainability at the top management level. This study examines how a CSO on the management board influences the quantity and quality of sustainability reports. While quantity is measured by the amount of information disclosed (sustainability disclosure), quality is measured as the decision for external assurance of the sustainability report, using the Global Reporting Initiative (GRI) guidelines as a reporting framework and publishing a combined report. Using a sample of German listed companies for the years 2017–2020, regression analysis is first conducted to analyse the impact of CSOs on sustainability reports. Second, the study shows how a chief executive officer (CEO) and a chief financial officer (CFO) impact sustainability reports when they also serve as CSOs. The results suggest that CSOs improve sustainability disclosure. In addition, a CSO positively impacts the decision for external assurance of the sustainability report but shows no impact on using the GRI guidelines and publishing a combined report. The results also show that a CFO positively influences sustainability disclosure, while a CEO does not. This study contributes to the growing literature on sustainable governance and how having a CSO on the management board impacts sustainability reporting. The study has numerous implications for regulators and practitioners. The most important insight is which management position should be responsible for sustainability to improve reporting and the limitations of that decision.
Keywords: 330; board structure; CSO; sustainability management; sustainability reporting; sustainable governance